The relationship between intimate partner violence reported at the first antenatal booking visit and obstetric and perinatal outcomes in an ethnically diverse group of Australian pregnant women: a population-based study over 10 years - Charlene Thornton; Virginia Schmied; Ana María Muñoz; Hannah Grace Dahlen (BMJ Open)
Objectives Intimate partner violence (IPV) is a global health issue affecting mainly women and is known to escalate during pregnancy and impact negatively on obstetric and perinatal outcomes. The aim of this study is to determine the incidence of IPV in a pregnant multicultural population and to determine the relationship between IPV reported at booking interview and maternal and perinatal outcomes.Design This is a retrospective population-based data study. We analysed routinely collected data (2006–2016) from the ObstetriX system on a cohort of pregnant women.Setting and participants 33 542 women giving birth in a major health facility in Western Sydney.Primary outcomes Incidence of IPV, association with IPV and other psychosocial variables and maternal and perinatal outcomes.Result 4.3% of pregnant women reported a history of IPV when asked during the routine psychosocial assessment. Fifty-four per cent were not born in Australia, and this had increased significantly over the decade. Women born in New Zealand (7.2%) and Sudan (9.1%) were most likely to report IPV at the antenatal booking visit, with women from China and India least likely to report IPV. Women who reported IPV were more likely to report additional psychosocial concerns including Edinburgh Postnatal Depression Scale scores >13 (7.6%), thoughts of self-harm (2.4%), childhood abuse (23.6%), and a history of anxiety and depression (34.2%). Women who reported IPV were more likely to be Australian born, smoke and be multiparous and to have been admitted for threatened preterm labour (Adjusted Odds Ratio (AOR) 1.8, 95% CI 1.28 to 2.39).Conclusions A report of IPV at the first antenatal booking visit is associated with a higher level of reporting on all psychosocial risks, higher antenatal admissions, especially for threatened preterm labour. More research is needed regarding the effectiveness of current IPV screening for women from other countries.